EFEKTIVITAS GAME JEKO (JELAJAH EKONOMI) BERBASIS STAD TERHADAP KEMAMPUAN PEMECAHAN MASALAH EKONOMI SISWA - Nurlaila Nurlaila; Sri Hardianti Sartika; Iis Aisyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to assess the effectiveness of the use of the Jeko Game (Economic Exploration) based on the STAD cooperative learning model in improving students' economic problem-solving abilities. The research method uses a quantitative approach with a quasi-experimental design, involving two classes of XI at SMA Negeri 1 Cihaurbeuti, and using an essay test as an instrument. Data analysis was carried out using the paired sample t-test and independent sample t-test at a significance level of 5%. The N-Gain Score in the experimental class reached 0.7147, while the control class was 0.6390, with an effect size of 0.79 which is included in the moderate category. The results showed a significant difference in increasing problem-solving abilities between the experimental and control classes, with a significance value (2-tailed) of 0.001. Thus, the use of the Jeko Game based on STAD is proven to be more effective than the Think-Pair-Share model in improving students' economic problem-solving abilities.